Social cooperative as a dynamically developing social enterprise (Economic and Political Thought, 2020)
The aim of the article is to present the dynamics of the formation of socialcooperatives and their possibilities in the socioeconomic sphere.Social cooperatives are a type of social economy entities in Poland. At thesame time, they constitute an entity closest to and most often classified as a socialenterprise due to its social mission as well as a part of the profit allocated for thispurpose. The Polish state still has difficulties in introducing social market economyand social transfers are not able to solve all the problems because this conceptworks only when it is not treated randomly and is applied in accordance withthe rules, i.e. coherently, in the long term and above all in the categories of theeconomic order. As a result, as well as in the face of socioeconomic problemsthat the epidemic will generate, the authors of the study see a social cooperativeas a social enterprise that is an entity helping the state to deal with such problemsas unemployment, homelessness or disability.
Keywords: social cooperative, social enterprise, social market economy